Pedagogical potential of immersive technology for English speaking learning - Jannah, Nita Maghfiratul; Afrezah, Novela Nur; Margana, Margana (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2023)
The use of immersive technology as a technological future digital multimodal in English learning has emerged in a new era of cybergogy. By optimizing various senses, student center learning, and autonomous learning strategy, effective learning is believed to improve significantly. Therefore, this article aimed to discuss the pedagogical potential of immersive technology in implementing English language learning, mainly speaking skills. By adapting this technology, not only cognitive skills are obtained, but also social skills can develop properly. Technology that promotes students' learning centers and accommodates various learning styles helps educators deal with problems in class. Various kinds of advantages and disadvantages of immersive technology are presented in this article. To take various benefits offered by the innovation of metaverse learning media, readiness in management and facilities need to be prepared for is explained. It recommends the concepts applied in schools to find out the dynamics of the main concepts needed in implementing digital multimodal in English-speaking learning.